Atividade física em profissionais de saúde do Sul e Nordeste do Brasil Physical activity among health professionals from South and Northeast Brazil - Fernando Carlos Vinholes Siqueira; Markus Vinícius Nahas; Luiz Augusto Facchini; Roberto Xavier Piccini; Elaine Tomasi; Elaine Thumé; Denise Silva da Silveira; Pedro C. Hallal (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
Foi realizado um estudo transversal, em 240 unidades básicas de saúde (UBS) dos modelos tradicional de assistência ou vinculadas ao Programa Saúde da Família (PSF), envolvendo 3.347 profissionais de saúde, que responderam ao Questionário Internacional de Atividade Física. A prevalência de sedentarismo (< 150 minutos por semana) foi de 27,5% (IC95%: 25,9-29,0). O sedentarismo foi mais freqüente nos profissionais do modelo tradicional, sendo tal diferença explicada pela presença dos agentes comunitários de saúde, cuja ocupação é bastante ativa apenas no modelo PSF. Houve maior percentual de sedentarismo nos profissionais que trabalham em municípios de grande porte e possuem alto nível sócio-econômico. Destaca-se a importância de projetos de capacitação de profissionais de saúde para a orientação e a prática de atividade física e a articulação entre profissionais de UBS e educadores físicos. This cross-sectional study analyzed 240 primary healthcare units, linked either to the traditional primary care model or the Family Health Program (FHP), involving a total of 3,347 health professionals who answered the International Physical Activity Questionnaire. Prevalence of sedentary lifestyle (< 150 minutes of physical activity per week) was 27.5% (95%CI: 25.9-29.0). Sedentary lifestyle was more frequent among health professionals in the traditional model, with the difference explained by the presence of community health agents, whose work only involves extensive physical activity in the FHP model. Sedentary health professionals were proportionally more common in large cities with better socioeconomic conditions. The study highlights the importance of education for health professionals aimed at orientation and practice in physical activities and collaboration between primary healthcare workers and physical education teachers.